Analisis Komparasi Potensi Kebangkrutan Perusahaan Ritel di Indonesia dengan Metode Altman Z-Score, Springate, dan Zmijewski - Annisa Aulia Puspa Anggraeni; Palti MT Sitorus (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2019)
The retail industry or retail trade experienced a slowdown in growth in early 2013 due to the weakening of the rupiah exchange rate, rising prices of raw materials, and the emergence of e-commerce that prevented the retail industry from developing. The impact is some retail companies closed their stores in 2017, so it can be caused bankruptcy. This study aims to determine the bankruptcy potential of 17 retail companies listed on the Indonesia Stock Exchange for the period 2012-2017 using Altman Z-score, Springate, and Zmijewski methods. The result is Altman Z-Score method has an accuracy rate of 33.3% in predicting bankruptcy. The Springate method has an accuracy rate of 63.6%, and the Zmijewski method has an accuracy rate of 61.1%. It means that in predicting the bankruptcy of a retail company, Springate method has the highest level of accuracy.